MANUSIA DALAM PERSPEKTIF ALQURAN (KAJIAN TEMATIK KISAH ADAM ALAIHISSALAM) - Abd Halim Nasution (Tazkiya: Jurnal Pendidikan Islam, 2021)
The view about human being has the main role in developing various theories how the human carried out. This study aims to know how the Quran represented the purpose and the role of the human potential from the story of Adam a.s.This study is conducted with analytic scientific approach using thematic method (maudu’i) investigating the history of Adam a.s in the Quran.The human as biological system (basyar) was inherited his anatomy and physic from Adam a.s. was desiring to biological needs, breeding and spreading, responsibility, as well as tending to make the destructive action. As khalifah, leader, ruler and prosperous of earth, God has given Adam and his descendants a spirit (ruh), knowledge potency to know, freedom and independence to do. However, the different side of human being tended to be a good and bad made a human constructively and destructively.The keywrods: Human, Adam a.s, Potency, Role